SOCIALIZATION OF THE USE OF SKYLIGHT ROOFS FOR LIGHTING IN RESIDENTIAL HOUSES IN FOBARU VILLAGE, NORTH TIDORE DISTRICT, TIDORE ISLANDS CITY - Ishak, Ishak; Rahim, Mustamin; Amali, Utdin Furqon (Ann Publisher, 2026)
Abstract: Background. Tidore Islands City in North Maluku Province faces limited access to natural lighting in residential houses, especially in coastal and hilly areas, as seen in Fobaharu. The simple design of houses with few openings leads people to rely heavily on artificial lighting even during the day, thereby increasing electricity consumption and economic burden, especially for low-income families. Initial surveys indicate limited public knowledge of skylight technology as an energy-efficient lighting solution. Aims. This program aims to reduce dependence on electricity by using sunlight, increase literacy in environmentally friendly technologies, and empower the community to develop skylight innovations as local business opportunities. Methods. The activities carried out include socialization and theory training. Conclusion. Despite obstacles to access to the location and to the mobilization of equipment, this program is expected to increase the community's knowledge, skills, and independence in using skylight technology to improve quality of life and encourage energy sustainability.